The transect method: a novel approach to on-farm welfare assessment of commercial turkeys. (9th January 2015) - Marchewka, Joanna; Estevez, Inma; Vezzoli, Giuseppe; Ferrante, Valentina; Makagon, Maja M.
Abstract : Currently, no animal-based protocol for on-farm welfare assessment of commercial turkeys is available. The birds' size and flighty nature make obtaining a representative sample using traditional methods difficult. The transect walks (TW) approach provides a potential alternative for on-farm assessments of turkey welfare. We compared the TW approach with a traditional method, and data collected as the birds were moved out of the house during the load out process (L). Ten commercial 19- to 20-week-old Hybrid turkey flocks were evaluated (1 flock/house/farm). Half of the flocks were housed on farms deemed as "faring well" by the company, the other half were on "suboptimal" farms. Each house was subdivided longitudinally into 4 transects. Two observers walked the transects in random order, recording the total number of birds per transect that were immobile; lame; aggressive towards a mate; interacting with humans; with visible head, vent, or back wounds; engaging in mounting behaviors; small; featherless; dirty; sick; terminal; or dead. Flocks were re-evaluated on the same day using the individual sampling method (S), where randomly selected birds were scored as they took 10 steps. Flocks were re-assessed within 48 h of the transect evaluation, as birds were funneled out of the house during load out. Using ANOVAs we determined the effects of observers, method, management, and their interactions on proportions of turkeys per house within each category. Outcome parameters were not affected by management ( P > 0.05 for all) or observer ( P > 0.05 for most), but an assessment method effect was detected ( P < 0.05). S differed from the 2 other methods ( P < 0.05) for most parameters except aggression towards a mate, back wounds, dirty, sick, and vent wounds. Differences were not detected between data collected using TW and during L, except for dead ( P = 0.0007) and immobile ( P = 0.007). Results suggest that the TW method is a promising tool for on-farm turkey welfare assessment as it produced results similar to those obtained at L when all birds could be scored individually.